New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae) - Sun, Chang-Hai (Zootaxa, 2016)
Four new species of Rhyacophila, R. acanthoida n. sp., R. tongmuensis n. sp., R. shiliae n. sp., and R. bisbifida n. sp., are diagnosed, described, and illustrated. Two species, R. inaequalis Denning & Schmid and R. manicata Kimmins are found to be new records for China. Remarks on six Species Groups, to which the four new species and two newly recorded species belong, are presented. New collection data are added for R. bidens Kimmins, R. claviforma Sun & Yang, R. haplostephana Sun & Yang, R. quadrifida Sun & Yang, and R. tetracantha Sun & Yang.